SUPPLY CHAIN MANAGEMENT OF AGRO-SAFETY TOURISM ALONG THE ING RIVER ROUTE, THAILAND - Muenwongthep, Theerut (International Journal of Supply Chain Management, 2019)
The management of agro-safety tourism is mostly focused on policies; however, there is a lack of coordination and integration of stakeholders in all sectors involved in the supply chain. This research aims to 1) study the supply chain management of agro-safety tourism in the route of the Ing River 2) evaluate the efficiency of the supply chain management of agro-safety tourism in the route of the Ing River and 3) propose guidelines for the supply chain management of agro-safety tourism in the route of the Ing River. It is a mixed research approach which conducted 387 questioners and 27 interviews with participants who are involved in the supply chain management of agro-safety tourism in the route of the Ing River. This paper found that the management of the supply chain of agro-safety tourism in the route of the Ing River have an impact on the efficiency of the supply chain management of agro-safety tourism in the route of the Ing River. It consists of four important processes, namely 1) delivery process consists of 10 sub-guidelines, 2) pre-delivery support process consists of 6 sub-guidelines, 3) post-delivery support process consists of 1 sub-guideline, and 4) the purchasing decision process consists of 2 sub-guidelines.